The phylogenetic position of Gallinuloides Eastman (Aves: Galliformes) from the Tertiary of North America - Dyke, Gareth J. (Zootaxa, 2003)
I have extended a recent phylogenetic analysis of morphological characters for galliform birds (pheasants, grouse, partridges and allies) to investigate the placement of the enigmatic fossil Gallinuloides wyomingensis Eastman. This analysis shows that, contrary to most previous interpretations, the fossil Gallinuloides is a basal member of the ‘phasianoid’ assemblage within Galliformes—not basal within the order as has been previously proposed. This conclusion is supported by several clear osteological features preserved on the holotype and only currently described specimen of this enigmatic fossil bird. Resolving the evolutionary relationships of Gallinuloides is of importance because this fossil taxon has proved a key player in debates regarding the timing of the diversification of all modern birds (Neornithes)—Gallinuloides has been used as both an internal and external fossil calibration point for molecular clock hypotheses dealing with the pattern and timing of the neornithine evolutionary radiation.